How to Hit Mesenchymal Stromal Cells and Make the Tumor Microenvironment Immunostimulant Rather Than Immunosuppressive - Poggi, Alessandro; Varesano, Serena; Zocchi, Maria Raffaella (Frontiers in Immunology, 2018)
Experimental evidence indicates that mesenchymal stromal cells (MSC) may regulate tumor microenvironment (TME). It is conceivable that the interaction with MSC can influence neoplastic cellfunctional behaviour,remodelling TME and generating a tumor cell niche that supports tissue neovascularization, tumor invasion and metastatization. In addition, MSC can release transforming growth factor-beta which is involved in the epithelial mesenchymal transition of carcinoma cells;this transition is essential to give rise to aggressive tumor cells and favour cancer progression. Also, MSC can both affect the anti-tumor immune response and limit drug availability surrounding tumor cells, thus creating a sort of barrier . This mechanism, in principle, should limit tumor expansion but, on the contrary, often leads to the impairment of the immune system-mediated recognition of tumor cells. Furthermore, the cross-talk between MSC and anti-tumor lymphocytes of the innate and adaptive arms of the immune system, strongly drives TME to become immunosuppressive. Indeed, MSC can trigger the generation of several types of regulatory cells which block immune response and eventually impair the elimination of tumor cells. Based on these considerations, it should be possible to favor the anti-tumor immune response acting on TME. First, we will review the molecular mechanisms involved in MSC-mediated regulation of immune response. Second, we will focus on the experimental data supporting that it is possible to convert TME from immunosuppressive to immunostimulant, specifically targeting MSC.